Case-based reasoning research and development : 27th international conference, ICCBR 2019, Otzenhausen, Germany, September 8-12, 2019 : proceedings /: 27th international conference, ICCBR 2019, Otzenhausen, Germany, September 8-12, 2019 : proceedings. ([2019]) - Unknown
No abstract available